Peripubertal plasma progesterone patterns in Ethiopian Menze ewe lambs - Mukasa-Mugerwa, E.; Mutiga, E.R. (1993)
Plasma progesterone concentrations were determined every 10 days for 38 grazing Menz ewe lambs from weaning until conception. Lambs were either fed extra supplementry concentrates and/or drenched for endoparasites. Inadequate nutrition delayed puberty onset by 4 to 5 months. Progesterone concentrations, determined by the ELISA technique, were basal before puberty. Subsequently, 63 percent lambs exhibited a `silent ovulation' prior to first behavioural oestrus but, transient rises of progesterone were not observed in 45 percent of lambs conceiving at first mating. Further, first oestrous was unovulatory (non-pubertal) in 21.1 percent of animals which may bias estimates of puberty onset based only on first oestrous behaviour. 5 percent of lambs exhibited a gestational oestrous.